Lichen Depsidones with Biological Interest - Ureña-Vacas, Isabel; González-Burgos, Elena; Divakar, Pradeep Kumar; Gómez-Serranillos, M. Pilar (Planta Medica, 2021)
Depsidones are some of the most abundant secondary metabolites produced by lichens. These compounds have aroused great pharmacological interest due to their activities as antioxidants, antimicrobial, and cytotoxic agents. Hence, this paper aims to provide up-to-date knowledge including an overview of the potential biological interest of lichen depsidones. So far, the most studied depsidones are fumarprotocetraric acid, lobaric acid, norstictic acid, physodic acid, salazinic acid, and stictic acid. Their pharmacological activities have been mainly investigated in in vitro studies and, to a lesser extent, in in vivo studies. No clinical trials have been performed yet. Depsidones are promising cytotoxic agents that act against different cell lines of animal and human origin. Moreover, these compounds have shown antimicrobial activity against both Gram-positive and Gram-negative bacteria and fungi, mainly Candida spp. Furthermore, depsidones have antioxidant properties as revealed in oxidative stress in vitro and in vivo models. Future research should be focused on further investigating the mechanism of action of depsidones and in evaluating new potential actions as well as other depsidones that have not been studied yet from a pharmacological perspective. Likewise, more in vivo studies are prerequisite, and clinical trials for the most promising depsidones are encouraged.
Keywords: secondary metabolites; natural products; pharmacology; antioxidants; antimicrobial; cytotoxic